2021
DOI: 10.3390/biomedicines9080868
|View full text |Cite
|
Sign up to set email alerts
|

Immune Assessment of BNT162b2 m-RNA-Spike Based Vaccine Response in Adults

Abstract: Vaccine efficacy is based on clinical data. Currently, the assessment of immune response after SARS-CoV-2 vaccination is scarce. A total of 52 healthcare workers were immunized with the same lot of BNT162b2 vaccine. The immunological response against the vaccine was tested using a T-specific assay based on the expression of CD25 and CD134 after stimulation with anti-N, -S, and -M specific peptides of SARS-CoV-2. Moreover, IgG anti-S2 and -RBD antibodies were detected using ELISA. Furthermore, the cell subsets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…Serological findings of this cohort were comparable with those described by other groups that studied serology up to 32 weeks after receiving the BNT162b2 vaccine [44][45][46][47][48][49][50][51][52]. Of note, many of these studies monitored vaccine-induced antibody responses in either patients with multiple pathologies (e.g., multiple sclerosis, hemodialysis) [44][45][46]53,54], SARS-CoV-2 convalescent patients [55][56][57] or between patients receiving one, two or three doses of the BNT162b2 vaccine [57,58].…”
Section: Discussionsupporting
confidence: 82%
“…Serological findings of this cohort were comparable with those described by other groups that studied serology up to 32 weeks after receiving the BNT162b2 vaccine [44][45][46][47][48][49][50][51][52]. Of note, many of these studies monitored vaccine-induced antibody responses in either patients with multiple pathologies (e.g., multiple sclerosis, hemodialysis) [44][45][46]53,54], SARS-CoV-2 convalescent patients [55][56][57] or between patients receiving one, two or three doses of the BNT162b2 vaccine [57,58].…”
Section: Discussionsupporting
confidence: 82%
“…Anti-RBD IGG S1 antibodies were lost in almost half of the participants at 10 months. These data are consistent with those observed in our and other studies that studied serology up to 32 weeks after receiving mRNA vaccines [36][37][38]. Other studies have reported the clinical performance of the Abbott trial [31,35,39] with results similar to ours.…”
Section: Discussionsupporting
confidence: 93%
“…The specific cellular immune response against vaccination was assessed as previously described [13]. Briefly, peripheral blood mononuclear cells (PBMCs) from sodiumheparinized blood were isolated by Ficoll gradient and cultured at 10 6 /mL in TexMACS medium (MiltenyiBiotec, BergischGladbach, Germany) during 24 h at 37 • C in a flat-bottom 96-well plate in 0.1% DMSO, PepTivator SARS-CoV-2 Prot S, Prot M and Prot N (1 and Dynabeads Human T activator CD3/CD28 (GibcoThermo Fisher Scientific Baltics UAB, Lithuania) as a positive control.…”
Section: Sars-cov-2 T-specific Response Assessment By Flow Cytometrymentioning
confidence: 99%
“…The results were expressed as the frequency in the activation induced molecules (CD25 + CD134 + ) ratio obtained after specific activation to negative non-stimulated control. A ratio > 3 in one of the specific SARS-CoV-2 peptides was considered positive as previously described [13], and representative examples are summarized in Figure S1.…”
Section: Sars-cov-2 T-specific Response Assessment By Flow Cytometrymentioning
confidence: 99%